Multi-component composite modified geopolymer material and preparation method thereof
Through the multi-component modified geopolymer material and its preparation method, the brittleness and durability of geopolymer materials are solved, and the flexural strength and durability are significantly improved, which is suitable for the engineering application of green building materials.
Patent Information
- Application Number
- CN202510845045.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-23
- Publication Date
- 2025-08-26
AI Technical Summary
The existing polymer materials have high brittleness, low flexural strength and insufficient self-healing ability, resulting in prone to cracking under load and deterioration of durability under environmental factors such as freeze-thaw cycles.
The three-dimensional reinforcement network is used to form a three-dimensional reinforcement network to build a cross-scale stress transmission and crack blocking network through multi-dimensional coordinated modification, combined with solid phase premix, liquid phase excitation and functional phase gradient incorporation.
The flexural strength and durability are significantly improved, the flexural strength is increased by 19.5%-29.3%, and the mass loss rate after freeze-thaw cycle is reduced by 49.1%. The material shows excellent service stability in harsh environments.
Smart Images

Figure CN120535248A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of engineering materials, and in particular to a multi-component composite modified geopolymer material and a preparation method thereof. Background Art
[0002] Existing geopolymer materials have two major technical bottlenecks: first, they are brittle, with flexural strength generally below 5 MPa, and are prone to microcracks under load; second, they lack self-healing ability, making it difficult to effectively repair cracks exceeding 100 μm in width. Under the influence of environmental factors such as freeze-thaw cycles and alternating wet and dry conditions, these microcracks will expand to form through-cracks, causing the material's permeability coefficient to increase by 2-3 orders of magnitude, ultimately leading to a deterioration in structural durability. Although studies have attempted to improve toughness through steel fiber reinforcement and polymer modification, conventional modification methods often have problems such as poor material compatibility, complex processes, or excessive costs. For example, when metal fiber addition exceeds 2%, the fluidity of the slurry is likely to decrease, while organic polymer modification is often accompanied by side effects such as reduced high-temperature resistance.
[0003] The information disclosed in this background technology section is only used to deepen the understanding of the background technology of the present disclosure and should not be regarded as an admission or any form of suggestion that the information constitutes the prior art known to those skilled in the art. Summary of the Invention
[0004] The present application provides a multi-component composite modified geopolymer material and a preparation method thereof, aiming to solve the core technical problems of traditional geopolymer materials such as high brittleness, easy cracking and poor durability.
[0005] According to one aspect of the present disclosure, a multi-component composite modified geopolymer material is provided, which is made from the following raw materials in parts by weight: 300 parts of carbonized steel slag, 20-50 parts of volcanic ash, 30-60 parts of slag powder, 5-10 parts of rice husk ash, 0.003-0.015 parts of CVD silicon oxide-based graphene, 0.05-0.1 parts of polyamide resin, 0.15-0.30 parts of copper fiber, and 18-22 parts of alkali activator.
[0006] In some embodiments of the present disclosure, the composite modified geopolymer material is made of the following raw materials in parts by weight: 300 parts of carbonized steel slag, 40 parts of volcanic ash, 50 parts of slag powder, 7.5 parts of rice husk ash, 0.005 parts of CVD silicon oxide-based graphene, 0.075 parts of polyamide resin, 0.2 parts of copper fiber, and 20 parts of alkali activator.
[0007] In some embodiments of the present disclosure, the carbonized steel slag is shale carbonized steel slag with a particle size of 5 to 20 mm.
[0008] In some embodiments of the present disclosure, the volcanic ash is Class II volcanic ash.
[0009] In some embodiments of the present disclosure, the slag powder is S95 grade slag powder.
[0010] In some embodiments of the present disclosure, the purity of the CVD silicon oxide substrate graphene is 95%.
[0011] In some embodiments of the present disclosure, the copper fiber is of cutting type.
[0012] In some embodiments of the present disclosure, the alkaline activator is prepared by mixing 25% LiOH solution and 15% Na2CO3 solution in a volume ratio of 3-5:1.
[0013] According to another aspect of the present disclosure, a method for preparing the composite modified geopolymer material is provided, comprising the following steps: (1) Prepare carbonized steel slag, volcanic ash, slag powder, rice husk ash, alkali activator and copper fiber according to the above weight proportions; (2) Dry-mixing carbonized steel slag, volcanic ash, slag powder, rice husk ash, and copper fiber for 1 to 2 minutes, then adding 80 to 120 parts of water and an alkali activator and stirring for 2 to 3 minutes. Finally, adding CVD silicon oxide-based graphene and polyamide resin to the mixture and stirring to form a uniform slurry; (3) Inject the slurry into the mold coated with polyalphaolefin and pre-cure the mold under standard conditions; (4) After pre-curing for 20 to 25 hours, demould and perform standard curing in an environment of 18 to 25°C and 95% RH for the specified time (such as 6 days, 27 days, 89 days, etc.).
[0014] In some embodiments of the present disclosure, in step (3), the pre-curing conditions are: temperature 58-62°C, relative humidity 94-96%.
[0015] The composite modified geopolymer material of the present invention achieves a breakthrough improvement in material performance through a multi-dimensional synergistic modification mechanism, which is specifically reflected in the following aspects: 1. Double breakthrough in environmental friendliness and performance improvement: Using industrial solid waste (carbonized steel slag, slag powder, etc.) and combining it with a pollution-free wet molding process, it significantly reduces carbon emissions compared to traditional cement. By introducing copper fibers (aspect ratio 50-80) and CVD silicon oxide-based graphene (specific surface area > 300m 2 / g) forms a three-dimensional reinforced network, which greatly improves the flexural strength. The mass loss rate after 300 freeze-thaw cycles is less than 1.5%, solving the industry problem of insufficient mechanical properties of environmentally friendly materials.
[0016] 2. Multi-scale structural synergistic toughening: Copper fibers (20-50μm diameter) act as macroscopic reinforcements to bear the primary stress, polyamide resin (viscosity 5000-8000cP) buffers stress concentration through molecular chain entanglement, and graphene sheets (3-5nm thickness) fill micropores at the nanoscale. During the alkaline excitation process, these three components form a "steel strand-rubber pad-nanomesh" composite structure, significantly enhancing crack propagation energy and reducing drying shrinkage to below 0.015%, achieving crack retardation from millimeter to nanometer scales.
[0017] 3. Self-Optimizing Preparation Process System: This innovative three-stage process utilizes "solid-phase premixing - liquid-phase excitation - functional phase gradient incorporation." By pre-dispersing copper fibers during the dry-mixing stage and incorporating graphene before final setting, it overcomes the fiber agglomeration and premature hydration of nanomaterials encountered in traditional processes. Combined with the viscosity-regulating properties of the polyamide resin, the slurry fluidity is maintained at 180 ± 10 mm, ensuring the feasibility of industrialized construction.
[0018] The technical benefits of this invention stem from a dual breakthrough in both material systems and process innovation: In terms of component design, a cross-scale stress transfer and crack retardation network is constructed through the synergistic interaction of metal fibers, polymers, and nanomaterials. In terms of process control, a phased functional composite preparation method is established based on the differences in the physicochemical properties of the components. This innovative "material-process" matching enables geopolymer materials to maintain their environmental advantages while achieving durability indicators that meet the Class II requirements of the JC / T2537-2019 standard, providing a reliable solution for the engineering application of green building materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 These are test diagrams of the composite modified geopolymer material in the embodiments of the present application, wherein a is an unconfined compressive strength test, b is the failure of the compressive specimen, c is a splitting test, d is the failure morphology of the compressive specimen, and e is a shrinkage test. DETAILED DESCRIPTION
[0020] The specific embodiments of the present invention are described below with reference to the examples. However, the following examples are only used to illustrate the present invention in detail and are not intended to limit the scope of the present invention in any way.
[0021] Unless otherwise specified, the instruments and equipment involved in the following examples are all conventional instruments and equipment; unless otherwise specified, the industrial raw materials involved are all commercially available conventional industrial raw materials.
[0022] The preparation of the multi-component composite modified geopolymer material in the following examples includes the following steps: Carbonized steel slag (provided by Anda Mineral Powder Factory), volcanic ash, slag powder, rice husk ash, CVD silicon oxide-based graphene (provided by Xianfeng Nanomaterial Technology Co., Ltd.), polyamide resin (provided by Shandong Longhua New Materials Co., Ltd.), copper fiber (provided by Changzhou Yaobang Friction Material Factory), and alkali activator were prepared according to the corresponding raw material ratios in each example.
[0023] (1) Weigh the specified mass of carbonized steel slag, volcanic ash, slag powder, and rice husk ash, prepare the alkali activator, and prepare the predetermined copper fiber.
[0024] Among them, the prepared copper fiber should first convert the specified volume fraction value into mass fraction and then be weighed; the alkaline activator is prepared by mixing 25% LiOH solution and 15% Na2CO3 solution in a ratio of 4:1 at 22.0±0.5℃, and after stirring evenly, it must be cooled to room temperature before pouring into the mixture.
[0025] (2) Carbonized steel slag, volcanic ash, slag powder, rice husk ash and copper fiber were mixed and dry-blended for 1-2 minutes, and then 100 parts of water and an alkali activator were added and stirred for 3 minutes. Finally, the corresponding amount of CVD silicon oxide-based graphene and polyamide resin were added to the mixture to form a uniform slurry; (3) Inject the slurry into the mold coated with polyalphaolefin and pre-cure the mold in an environment of 60±1.0℃ and 95±0.5%RH for 24h; (4) After pre-curing, demoulding is performed and the molded specimens are cured under standard conditions of 20°C and 95% RH for 6 days, 27 days or 89 days to obtain the composite modified geopolymer material.
[0026] Example 1: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of shale carbonized steel slag (particle size of 5~20mm), 40 parts of grade II volcanic ash, 30 parts of S95 grade slag powder, 6 parts of rice husk ash, 0.005 parts of CVD silicon oxide-based graphene (purity 95%), 0.06 parts of polyamide resin, 0.15 parts of copper fiber (cutting type), and 20 parts of alkali activator.
[0027] Example 2: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of shale carbonized steel slag (particle size of 5~20mm), 40 parts of grade II volcanic ash, 40 parts of S95 grade slag powder, 7.5 parts of rice husk ash, 0.006 parts of CVD silicon oxide-based graphene (purity 95%), 0.075 parts of polyamide resin, 0.2 parts of copper fiber (cutting type), and 20 parts of alkali activator.
[0028] Example 3: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of shale carbonized steel slag (particle size of 5~20mm), 40 parts of grade II volcanic ash, 50 parts of S95 grade slag powder, 9 parts of rice husk ash, 0.007 parts of CVD silicon oxide-based graphene (purity 95%), 0.09 parts of polyamide resin, 0.25 parts of copper fiber (cutting type), and 20 parts of alkali activator.
[0029] Example 4: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of shale carbonized steel slag (particle size of 5~20mm), 50 parts of grade II volcanic ash, 30 parts of S95 grade slag powder, 6 parts of rice husk ash, 0.005 parts of CVD silicon oxide-based graphene (purity 95%), 0.06 parts of polyamide resin, 0.15 parts of copper fiber (cutting type), and 20 parts of alkali activator.
[0030] Example 5: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of shale carbonized steel slag (particle size of 5~20mm), 50 parts of grade II volcanic ash, 40 parts of S95 grade slag powder, 7.5 parts of rice husk ash, 0.006 parts of CVD silicon oxide-based graphene (purity 95%), 0.075 parts of polyamide resin, 0.2 parts of copper fiber (cutting type), and 20 parts of alkali activator.
[0031] Example 6: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of shale carbonized steel slag (particle size of 5~20mm), 50 parts of grade II volcanic ash, 50 parts of S95 grade slag powder, 9 parts of rice husk ash, 0.007 parts of CVD silicon oxide-based graphene (purity 95%), 0.09 parts of polyamide resin, 0.25 parts of copper fiber (cutting type), and 20 parts of alkali activator.
[0032] The composite modified geopolymer materials in Examples 1-6 were subjected to mechanical and durability tests, including flexural strength test, compressive strength test, splitting tensile strength test, drying shrinkage test and freeze-thaw cycle test. The test process is as follows: Figure 1 shown.
[0033] The performance of the composite modified geopolymer material of the present invention was tested and compared with that of ordinary geopolymer materials. The test results are shown in Table 1.
[0034] Table 1 Mechanical properties and durability test of composite modified geopolymer materials .
[0035] Based on the experimental data from Examples 1-6 (Table 1), the composite modified geopolymer material of the present invention demonstrates significant technological breakthroughs, the core of which stems from the synergistic effects of multiple components and the innovative design of the preparation process. The specific technical effects can be summarized into the following three aspects: 1. Systematic improvement of mechanical properties ① Breakthrough Increase in Flexural Strength: The average flexural strength of Examples 1-6 was 9.8 MPa (a 19.5% increase over conventional geopolymers), with Example 2 reaching 10.6 MPa (a 29.3% increase). This is due to the cross-scale synergy between copper fibers (20-50 μm in diameter) and graphene on a CVD silica substrate (3-5 nm in thickness): a. The copper fibers, acting as macroscopic reinforcements, effectively inhibit crack propagation through fiber bridging. Their aspect ratio (50-80) and interfacial bonding strength (>5 MPa) with the matrix are key to improving flexural strength. b. The graphene sheets form a network structure at the nanoscale, enhancing fracture toughness through crack deflection. The chemical bonding of their surface hydroxyl groups (-OH) with the geopolymer matrix further strengthens the interfacial bond.
[0036] ② Synergistic optimization of compressive and tensile properties: The average compressive strength of the examples is 59.2 MPa (a 6.7% increase over conventional geopolymers), and the average splitting tensile strength is 3.63 MPa (a 33.5% increase). Polyamide resin (viscosity 5000-8000 cP) plays a key role in this: a. Stress buffering effect: The flexible structure of the polyamide molecular chain absorbs impact energy and reduces stress concentration; b. Interface reinforcement: Its polar groups (-CONH-) form a hydrogen bond network with the geopolymer matrix, improving interfacial bonding strength (by approximately 40%).
[0037] 2. Significant improvement in durability ① A qualitative breakthrough in freeze-thaw resistance: The average mass loss rate after 100 freeze-thaw cycles in the example was 2.9% (a 49.1% reduction compared to conventional geopolymers). This is achieved through: a. Pore structure optimization: Graphene nanofilling reduces the porosity of conventional geopolymers from 18.3% to 12.5%, increasing the proportion of closed pores to 85%; b. Moisture migration inhibition: The three-dimensional network formed by the copper fibers blocks the flow of capillaries, and combined with the hydrophobic modification of the polyamide resin (increasing the contact angle to 105°), the water permeation path is extended by 3-5 times.
[0038] ② Breakthrough in the contradiction between shrinkage characteristics and durability: Although the average shrinkage coefficient of the examples is 15.1% (an increase of 38.9% compared with ordinary geopolymers), its mass loss rate is significantly reduced, indicating: a. Enhanced shrinkage controllability: The elastic modulus of polyamide resin (1.2-2.5 GPa) can buffer shrinkage stress and prevent crack propagation; b. Self-healing potential is revealed: Under alkaline excitation environment, the secondary reaction of graphene sheets and geopolymer gel can partially repair microcracks (SEM observation shows that the crack width is self-limited within 50 μm).
[0039] 3. Scientific attribution of technical effects ① Multi-scale structural coordination mechanism a. Macroscale: Copper fibers (1.5-2.0 vol%) form a "reinforced skeleton" to improve load transfer efficiency; b. Mesoscale: Polyamide resin (3-5 wt%) acts as a "flexible hinge" to balance stress distribution; c. Nanoscale: Graphene (0.05-0.1 wt%) acts as a "nano-rivet" to strengthen interfacial bonding.
[0040] ② Strong correlation between process and performance: The three-stage process (solid-phase premixing → liquid-phase excitation → gradient incorporation of functional phase) ensures the optimal interaction time for each component: a. Pre-dispersion of copper fiber through dry mixing (dispersion > 90%); b. Incorporation of graphene before final coagulation to avoid premature hydration; c. Post-incorporation of polyamide resin to achieve precise viscosity control (paste fluidity 180±10 mm).
[0041] The core breakthrough of this invention lies in the deep coupling of material design and process control, which addresses the industry's difficulty in achieving a synergistic improvement in the strength, toughness, and durability of traditional geopolymer materials. Despite an increase in shrinkage coefficient, the significant reduction in mass loss (<3.0%) demonstrates the material's superior service stability in practical engineering applications. According to JC / T2537-2019, "Technical Specification for Durability of Geopolymer Concrete," the durability index of the examples meets Level II (high durability) requirements, laying a technical foundation for the application of geopolymer materials in harsh environments (such as freeze-thaw areas and marine engineering).
[0042] The present application has been described in detail above with reference to the embodiments; however, those skilled in the art will appreciate that, without departing from the spirit of the present invention, the specific parameters in the above embodiments may be changed, or the relevant materials and method steps may be replaced by equivalents, thereby forming multiple specific embodiments, which are all within the common variation range of the present application and will not be described in detail here.
Claims
1. A multi-component composite modified geopolymer material, characterized in that: Made from the following raw materials in parts by weight: 300 parts of carbonized steel slag, 20-50 parts of volcanic ash, 30-60 parts of slag powder, 5-10 parts of rice husk ash, 0.003-0.015 parts of CVD silicon oxide-based graphene, 0.05-0.1 parts of polyamide resin, 0.15-0.30 parts of copper fiber, and 18-22 parts of alkali activator.
2. The multi-component composite modified geopolymer material according to claim 1, characterized in that: Made from the following ingredients: 300 parts of carbonized steel slag, 40 parts of volcanic ash, 50 parts of slag powder, 7.5 parts of rice husk ash, 0.005 parts of CVD silicon oxide-based graphene, 0.075 parts of polyamide resin, 0.2 parts of copper fiber, and 20 parts of alkali activator.
3. The composite modified geopolymer material according to claim 1, characterized in that: The carbonized steel slag is shale carbonized steel slag with a particle size of 5 to 20 mm.
4. The composite modified geopolymer material according to claim 1, characterized in that: The volcanic ash is Class II volcanic ash.
5. The composite modified geopolymer material according to claim 1, characterized in that: The slag powder is S95 grade slag powder.
6. The composite modified geopolymer material according to claim 1, characterized in that: The purity of the CVD silicon oxide substrate graphene is ≥95%.
7. The composite modified geopolymer material according to claim 1, characterized in that: The copper fiber is a cutting type copper fiber.
8. The composite modified geopolymer material according to claim 1, characterized in that: The alkaline activator is prepared by mixing 25% LiOH solution and 15% Na2CO3 solution in a volume ratio of 3-5:
1.
9. A method for preparing a composite modified geopolymer material, characterized in that: The steps include: (1) Prepare the raw materials according to the weight ratios in claim 1; (2) Dry-mixing carbonized steel slag, volcanic ash, slag powder, rice husk ash, and copper fiber for 1 to 2 minutes, then adding 80 to 120 parts of water and an alkali activator and stirring for 2 to 3 minutes. Finally, adding CVD silicon oxide-based graphene and polyamide resin to the mixture and stirring to form a uniform slurry; (3) Inject the slurry into the mold coated with polyalphaolefin and pre-cured under standard conditions; (4) After pre-curing for 20 to 25 hours, demould and then perform standard curing in an environment of 18 to 25°C and 95% RH until the specified age.
10. The preparation method according to claim 9, characterized in that In step (3), the pre-curing conditions are: temperature 58-62°C, relative humidity 94-96%.
Citation Information
Cited By
Resource evaluation method and system for graphite mine mining
CN121903410A
A resource assessment method and system for graphite mining
CN121903410B